Forensic Monitoring Project Report: Livac Exhumations State Commission on Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Connor, Melissa The State Commission on Missing Persons (Bosniak) recovered the burned remains of one man on 15 June 1998 in Livac. Place of Exhumation: Livac Date of Exhumation: 15 June 1998 Minimum Number of Exhumed Individuals: 001